Exploring the Effect and Molecular Docking Interaction of Carboxypeptidase and Amidohydrolase on Ochratoxin A and Zearalenone Degradation - Sulaiman A. Alsalamah; Mohammed Ibrahim Alghonaim; Abdu Ali Y. Moafa; Mukul Sharma (BioResources)
To keep consumers from the hazard of exposure to mycotoxins and meet the allowed limits, numerous physical and chemical approaches for eliminating Ochratoxin A (OTA) and Zearalenone (ZEN) have been studied. Enzymes technology, including carboxypeptidase and amidohydrolase, were evaluated on their ability to degrade OTA and ZEN. Two fungi, namely Aspergillus ochraceus and Fusarium graminearum, were isolated with their mycotoxins OTA and ZEN from contaminated yellow corn grains. Carboxypeptidase at 0.50 and 0.75 U/mL caused 33.3 and 57.7% degradation of OTA, and 27.1 and 57.2% degradation of ZEN, respectively. Amidohydrolase at 0.50 and 0.75 U/mL caused 68.0 and 76.9% degradation of OTA, and 26.7 and 53.7% degradation of ZEN, respectively. This study investigated the molecular docking interactions of carboxypeptidase (PDB ID: 3CPA) and amidohydrolase (PDB ID: 1QRE) with OTA and ZEN. Docking scores (S) and energy terms (E_conf, E_place, E_score1, E_refine, E_score2) were calculated to evaluate binding affinities. The OTA exhibited stronger docking scores (-6.00058 to -5.0568) compared to ZEN (-5.37388 to -4.4574), indicating higher thermodynamic stability. Key interactions, such as hydrogen bonds (H-donor/acceptor) and π-based interactions (H-pi/pi-H), were identified between ligands and active-site residues (e.g., ASN 185, LYS 51, and GLU 196).